1990
DOI: 10.1055/s-2007-1026475
|View full text |Cite
|
Sign up to set email alerts
|

Schwangerschaftsausgang unter intensivierter Insulintherapie bei manifestem Diabetes*

Abstract: In 1981, the intensified insulin therapy for achievement of euglycaemia in pregnant diabetics was introduced at the University Department of Obstetrics and Gynaecology in Cologne. This study compares the results of 112 pregnancies in women with overt diabetes monitored before (1971-1980) or after (1981-1988) changing the therapeutic regimen. In the period from 1981 to 1988, the proportion of euglycaemic patients (preconceptionally 19%, before delivery 79%) was clearly higher than from 1971 to 1980 (n = 42; 7% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

1993
1993
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 2 publications
0
6
0
2
Order By: Relevance
“…The main risk of strict metabolic control in 100M is severe maternal hypoglycaemia (20 to 40%) requiring intervention by another trained person (Bergmann et al 1987;Crombach et al 1990;Hillebrand et al 1990;Rayburn et al 1986;Steel et al 1989). So far, clinical studies have not presented any evidence that hypoglycaemia in early pregnancy is related to congenital malformations in humans (Mills et al 1988;Steel et al 1989).…”
Section: Objectives Indications Andmentioning
confidence: 99%
See 2 more Smart Citations
“…The main risk of strict metabolic control in 100M is severe maternal hypoglycaemia (20 to 40%) requiring intervention by another trained person (Bergmann et al 1987;Crombach et al 1990;Hillebrand et al 1990;Rayburn et al 1986;Steel et al 1989). So far, clinical studies have not presented any evidence that hypoglycaemia in early pregnancy is related to congenital malformations in humans (Mills et al 1988;Steel et al 1989).…”
Section: Objectives Indications Andmentioning
confidence: 99%
“…Target values for different laboratory parameters for strict metabolic control of pregnant diabetics; glucose levels in venous whole blood are generally 5 to 15% lower than those in capillary whole blood and in venous plasma (Diabetic Pregnancy Study Group 1989). Data summarised here are from Burkart et al (1986); Crombach et al (1990); Gabbe (1985); Hare (1991); Hofmann et al (1990); Jovanovic et al (1982); Somville (1990); Weiss, personal communication (1987) laboratory parameter/ level time period Capillary venous whole blood glucose (mg/dl) before breakfast 60-90 before lunch/supper, at bedtime 60-105 1 h after meal 70-140 2h after meal 2am to 6am mean day value HbA1 (%) HbA1c (%) Serum fructosamine (mmol/l) Amniotic fluid insulin (>28 gw) [mUll] 60-120 60-100 80-100 <7.0-7.5 <5.0-5.5 <2.6 <6-10 (10) Abbreviations: HbA1, HbA1C = glycosylated haemoglobin; gw = gestational weeks.…”
Section: Short-acting Insulinmentioning
confidence: 99%
See 1 more Smart Citation
“…Observational studies which looked at similar comparisons were also identified [28,32,33,35,49,50,75]. A cohort study by Huddle et al (2005) [50] focused on pregestational and gestational diabetes in a population of black women.…”
Section: Resultsmentioning
confidence: 99%
“…Although perinatal mortality can be decreased to 1-3% by tight metabolic control, perinatal morbidity is still high [6,27]. Fetal hyperinsulinism is considered to be the main pathogenetic mechanism for diabetes-specific neonatal complications (fetopathy, macrosomia, hypoglycemia).…”
Section: Introductionmentioning
confidence: 99%